Clinical outcome and intraprocedural characteristics of left atrial appendage occlusion: a comparison between single-occlusive plug-type and dual-occlusive disc-type devices - Primessnig, Uwe; Schrader, Helene; Wiedenhofer, Julia M.; Trippel, Tobias D.; Parwani, Abdul S.; Blaschke, Florian; Hindricks, Gerhard; Falk, Volkmar; Dreger, Henryk; Sherif, Mohammad; Boldt, Leif-Hendrik (Frontiers in Cardiovascular Medicine, 2024)
Background: Percutaneous interventional left atrial appendage occlusion (LAAO) is a reliable, safe and effective alternative for stroke prevention in selected patients with atrial fibrillation. Methods: In a retrospective observational study 149 patients underwent LAAO between 2016 and 2022 at the department of cardiology of the Charité – Universitätsmedizin Berlin, Campus Virchow with atrial fibrillation (AF) for prevention of thromboembolic complications. We compared patient characteristics, intraoperative details and postoperative outcomes between single-occlusive plug type (SOPT) and dual-occlusive disc type (DODT) devices. Results: In all patients, the device implantation was successful. 60 patients received a SOPT occluder, including Watchman (35%) and Watchman FLX Occluders (65%), while 89 patients received a DOPT occluder, including Amplatzer Cardiac Plug (37.1%), the Amplatzer Amulet (25.8%) and the LAmbre occluder (37.1%) systems. Procedure duration was significantly longer for DOPT occluder implantation (49±33 vs. 41±25 min, p=0.018). There were no in-hospital deaths or thromboembolic events reported after LAAO in both groups. Beyond that, a low rate of bleeding or access-side related complications and pericardial tamponades were observed. Anticoagulation at discharge varied. 60.8% of all patients received dual antiplatelet therapy at hospital discharge, 33.1% direct oral anticoagulants. A 6-month follow up could be obtained in 85% of the patients. All implanted devices were in desired position. However, in 5.7% a device-related thrombus formation could be detected in the SOPT group, while no thrombus could be seen in the DODT group (p = 0.11). Thromboembolic events were noticed in 3.1%, without any difference between the device types. There was a statisticially non-significant trend for less residual device leaks after SOPT vs. DODT implantation (no leak in 71.7% vs. 62.2%, p=0.07, minor leaks <5mm, 9.4% vs. 20.3%, p=0.1). In the SOPT group, less bleeding complications were reported after LAAO (11.3% vs. 17.6%, p=0.1). Conclusion: Our data suggest safety and efficiency of LAAO with a very high procedural implantation success rate irrespective of the used LAA device. Furthermore, no relevant procedural or device related complication occurred during the 6 month follow up in all patients.